The Hox cluster microRNA miR-615: a case study of intronic microRNA evolution - Quah, Shan (EvoDevo, 2015)
BACKGROUND: Introns represent a potentially rich source of existing transcription for the evolution of novel microRNAs (miRNAs). Within the Hox gene clusters, a miRNA gene, miR-615, is located within the intron of the Hoxc5 gene. This miRNA has a restricted phylogenetic distribution, providing an opportunity to examine the origin and evolution of a new miRNA within the intron of a developmentally-important homeobox gene. RESULTS: Alignment and structural analyses show that the sequence is highly conserved across eutherian mammals and absent in non-mammalian tetrapods. Marsupials possess a similar sequence which we predict will not be efficiently processed as a miRNA. Our analyses suggest that transcription of HOXC5 in humans is accompanied by expression of miR-615 in all cases, but that the miRNA can also be transcribed independently of its host gene through the use of an intragenic promoter. We present scenarios for the evolution of miR-615 through intronic exaptation, and speculate on the acquisition of independent transcriptional regulation. Target prediction and transcriptomic analyses suggest that the dominant product of miR-615 is involved in the regulation of growth and a range of developmental processes. CONCLUSIONS: The miR-615 gene evolved within the intron of Hoxc5 in the ancestor of placental mammals. Using miR-615 as a case study, we propose a model by which a functional miRNA can emerge within an intron gradually, by selection on secondary structure followed by evolution of an independent miRNA promoter. The location within a Hox gene intron is of particular interest as the miRNA is specific to placental mammals, is co-expressed with its host gene and may share complementary functions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13227-015-0027-1) contains supplementary material, which is available to authorized users.